Pengaruh pelatihan dan motivasi kerja guru terhadap kinerja guru di SMPN 5 Pelepat Ilir Muaro Bungo - Nurul Hikmah (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to determine the effect of training and work motivation on teacher performance at SMPN5 Pelepat Ilir Muaro Bungo. Respondents in this study amounted to 13 employees. Methods of data collection using literature study techniques, observation and questionnaires and measured with a likert scale. The data analysis technique in this study uses an analytical tool, namely SPSS Version 25. The result of this study indicated that (1) partially training has a significant positive effect on teacher performance (2) partially work motivation has a significant positive effect on teacher performance (3) Simultaneously training and motivation teacher work has a significant effect on teacher performance at SMPN5 Pelepat Ilir Muaro Bungo.